AN ANALYTICAL STUDY ON WORK LIFE BALANCE IN EMPLOYEE RETENTION WITH SPECIAL REFERENCE TO IT AND BPO SECTORS - Singh, Dr. Rajendra; Dubey, Ms. Khushbu (IJRDO - Journal of Applied Management Science, 2016)
In modern times, employee’s retention has become one of the leading challenges for organization, especially for service sector. The issue isn’t simply losing a key member of your team; there is also the hassle-and cost-of replacement. It is obvious that employee’s retention is one of the most pressing issues that Human Resource Professionals face today. This problem becomes critical when the employee is unable to maintain the balance between work life and family relationship. In that situation mostly employees leave the organization as they feel that in this organization their emotions, feelings and passions are not given recognition and their employers are not going to cooperate in any way. Hence, in this study, the effect of work life balance has been examined in lieu of the employee retention. Correlation and regression were applied to conclude the findings of this research study.